Nontargeted metabonomics analysis of Scorias spongiosa fruiting bodies at different growth stages - Nong, Xiang; Zhong, Shengnan; Huang, Lanying; Xiao, Jie; Hu, Ye; Xie, Yue (Frontiers in Microbiology, 2024)
Scorias spongiosa is an edible fungus. In this study, a nontargeted metabonomic analysis was conducted on the fruiting bodies of this fungus at five growth stages, and the differences in metabolites and the related metabolic pathways during growth and development were analysed. This study revealed that the five growth stages of S. spongiosa fruiting bodies were associated with 15 pathways. These 15 metabolic pathways are speculated to play important roles in the growth of S. spongiosa fruiting bodies. Eleven bioactive substances were identified among the differentially expressed compounds. The content of six bioactive substances was highest at the S1 growth stage among all the growth stages. The metabolites related to sugar metabolism were enriched in three main pathways: pentose and gluconate interconversions, the pentose phosphate pathway, and the citrate cycle (TCA cycle). These results suggested that the S1 growth stage can be selected as the harvest period of S. spongiosain fruiting bodies to retain most of the bioactive substances. Pentose and gluconate interconversions, the pentose phosphate pathway, and the TCA cycle are related to changes in polysaccharide content during the growth of S. spongiosa fruiting bodies.